2005
DOI: 10.1126/science.1116238
|View full text |Cite
|
Sign up to set email alerts
|

SLC24A5, a Putative Cation Exchanger, Affects Pigmentation in Zebrafish and Humans

Abstract: Lighter variations of pigmentation in humans are associated with diminished number, size, and density of melanosomes, the pigmented organelles of melanocytes. Here we show that zebrafish golden mutants share these melanosomal changes and that golden encodes a putative cation exchanger slc24a5 (nckx5) that localizes to an intracellular membrane, likely the melanosome or its precursor. The human ortholog is highly similar in sequence and functional in zebrafish. The evolutionarily conserved ancestral allele of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
863
1
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 946 publications
(928 citation statements)
references
References 33 publications
52
863
1
12
Order By: Relevance
“…These studies have identified several genes associated with skin pigmentation that displayed genetic signatures consistent with divergent positive selection [33,34] and with recent convergent evolution of a lighter pigmentation type in Europeans and East Asians [34]. Remarkably, variation at two of these loci is also responsible for pigment variation in the scales of fish [32,33].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies have identified several genes associated with skin pigmentation that displayed genetic signatures consistent with divergent positive selection [33,34] and with recent convergent evolution of a lighter pigmentation type in Europeans and East Asians [34]. Remarkably, variation at two of these loci is also responsible for pigment variation in the scales of fish [32,33].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 98%
“…However, multiple studies have identified genetic variants associated with lighter and darker skin pigmentation in humans [32][33][34], a trait that might be differentially selected in regions with low and high ultraviolet radiation (UVR), owing to known associations between skin pigmentation and vitamin D synthesis and protection from UVR [34,35]. These studies have identified several genes associated with skin pigmentation that displayed genetic signatures consistent with divergent positive selection [33,34] and with recent convergent evolution of a lighter pigmentation type in Europeans and East Asians [34].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 99%
“…9 Several genes were associated with various pigment traits long before the genome-wide association study era. [10][11][12][13][14][15][16] However, it is important to note that-unlike in the case of testing for many complex diseases 17 genome-wide association study has been particularly effective in association testing for human pigmentation and has confirmed already known, and revealed multiple new polymorphisms and loci involved in determination of human pigmentation. [18][19][20][21] This has been particularly striking in the case of variation in eye colour, which is assessed to be 50% explained by known polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…pour défi-nir les races. On sait par exemple que plusieurs gènes différents contribuent à une peau claire, SLC24A5 est celui qui est trouvé chez la majorité des Européens, mais n'est pas le seul [7]. La mutation de ce gène, impliquée dans la peau claire des Européens, est apparue récemment, il y a environ 7 000 ans ; auparavant, les populations européennes avaient la peau noire [8].…”
Section: La Question De L'existence De « Races »unclassified